2006
DOI: 10.1038/sj.ki.5000253
|View full text |Cite
|
Sign up to set email alerts
|

Vascular tone control in humans: Insights from studies in Bartter's/Gitelman's syndromes

Abstract: Studies in patients with Bartter's and Gitelman's syndromes performed in the last 10 years have provided important insights into the mechanistic details of relevant pathways of angiotensin II signaling and vascular tone regulation, therefore making these syndromes a good human model to gain insight into the mechanisms responsible for maintaining/controlling vascular tone. Extensive studies of patients with Bartter's/Gitelman's syndromes have, in fact, shown biochemical abnormalities of angiotensin II short- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 49 publications
(77 reference statements)
3
79
0
1
Order By: Relevance
“…For example, one could speculate that CD34+KDR+ cell phenotype may correlate with pathological vascular damage and increased CV risk, 48 while CD133+KDR+ and CD34+CD133+KDR+ are likely related to oxidative status and endothelial function as suggested by their status in BS/GS that is, increased CD133+KDR+ and CD34+CD133+KDR+ and unchanged CD34+KDR+, which fits with the biochemical, molecular and functional picture of good endothelial status reported in these patients. [16][17][18][19][20][21][22][23][26][27][28] In conclusion, the study documents in a human system that EPC numbers and specific populations are related to important clinical and biochemical factors involved in CV status. These results alongside the ongoing studies in our laboratory to quantitate calcitonin gene-related peptide and EPC status for example, senescence and proliferation in BS/GS, reaffirm the utility of BS/GS patients as a useful system to investigate EPC's role(s) in the pathophysiology of CV remodeling in humans.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, one could speculate that CD34+KDR+ cell phenotype may correlate with pathological vascular damage and increased CV risk, 48 while CD133+KDR+ and CD34+CD133+KDR+ are likely related to oxidative status and endothelial function as suggested by their status in BS/GS that is, increased CD133+KDR+ and CD34+CD133+KDR+ and unchanged CD34+KDR+, which fits with the biochemical, molecular and functional picture of good endothelial status reported in these patients. [16][17][18][19][20][21][22][23][26][27][28] In conclusion, the study documents in a human system that EPC numbers and specific populations are related to important clinical and biochemical factors involved in CV status. These results alongside the ongoing studies in our laboratory to quantitate calcitonin gene-related peptide and EPC status for example, senescence and proliferation in BS/GS, reaffirm the utility of BS/GS patients as a useful system to investigate EPC's role(s) in the pathophysiology of CV remodeling in humans.…”
Section: Discussionmentioning
confidence: 94%
“…15 The results of an extensive series of studies from our laboratory have provided mechanistic explanations for these patients' vascular hyporeactivity and absence of CV remodeling. [16][17][18][19][20] We have documented a blunted Ang II signaling and related pathways [21][22][23][24][25][26][27][28] in BS/GS patients. In addition, we have reported in BS/GS reduced oxidative stress alongside increased HO-1 gene expression, 29,30 upregulation of nitric oxide (NO) system 31,32 and increased NO-dependent vasodilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The possibility of confirming this mechanism in humans could come from the study of a human model for vascular tone and structure regulation, which has biochemical and hormonal characteristics typical of hypertension, yet shows hyporesponsiveness to pressors, reduced vascular resistance and normo/hypotension such as BS/GS. 5,6 Our extensive series of studies have, in fact, provided mechanistic explanations for the vascular hyporeactivity typical of these patients and also led us to propose that BS/GS is a good human model to explore the mechanisms responsible for Ang II signalling. 5,6 In BS/GS, we have demonstrated that the Ang II signalling pathway is blunted as documented by the increased regulator of G-protein signalling-2 gene and protein expression, reduced gene and protein expression of the a-subunit of the Gq-binding protein, which transduces Ang II signal, and reduced related downstream cellular events such as intracellular Ca 2 þ and IP 3 release and PKC activity.…”
mentioning
confidence: 99%
“…5,6 Our extensive series of studies have, in fact, provided mechanistic explanations for the vascular hyporeactivity typical of these patients and also led us to propose that BS/GS is a good human model to explore the mechanisms responsible for Ang II signalling. 5,6 In BS/GS, we have demonstrated that the Ang II signalling pathway is blunted as documented by the increased regulator of G-protein signalling-2 gene and protein expression, reduced gene and protein expression of the a-subunit of the Gq-binding protein, which transduces Ang II signal, and reduced related downstream cellular events such as intracellular Ca 2 þ and IP 3 release and PKC activity. 5,6 This abnormal G-protein-mediated signalling of Ang II shown in BS/GS patients, combined with downregulation of RhoA/Rho-kinase pathway 7 and upregulation of NO system, 5,6 reduced peripheral resistance, vascular hyporeactivity, normo/hypotension typical of these patients and their collection of biochemical characteristics, presents a mirror image of that found in hypertension.…”
mentioning
confidence: 99%